Extremely Light Carrier‐Effective Mass in a Distorted Simple Metal Oxide. (7th December 2018) - Kim, Gowoon; Zhang, Yu‐Qiao; Min, Taewon; Suh, Hoyoung; Jang, Jae Hyuck; Kong, Hyeonjun; Lee, Joonhyuk; Lee, Jaekwang; Jeon, Tae‐Yeol; Lee, Inwon; Cho, Jinhyung; Ohta, Hiromichi; et al.
Abstract: Exotic electron transport properties such as quasi 1D conductivity are useful to realize advanced electronic devices showing unique properties. Anisotropic electron transport properties are often found in complex metal oxides due to their complicated crystal structures. Although simple metal oxides with distorted crystal structures could also be expected to show anisotropic electron transport properties, it is rarely studied most likely due to the lack of their high‐quality epitaxial films. Here anisotropic electron transport properties, showing "fast electron transport path, " in a simple distorted metal oxide, NbO2, is reported. High‐quality NbO2 epitaxial films with different crystallographic orientations on (0001) and (1 1 ¯ 02) α‐Al2 O3 single crystal substrates are fabricated, and the electron transport properties at room temperature are measured. Both the resistivity and absolute value of the thermopower along the [11 2 ¯ ] NbO2 is pretty small as compared with other directions. Experimentally obtained electron carrier effective mass in the [11 2 ¯ ] direction is surprisingly small, only 0.051 me, which is similar to that of high‐mobility GaAs. Since simple metal oxides have several advantages against complex oxides in view of easy fabrication, the present results will be beneficial for realizing advanced electronic devices using simple metal oxides. Abstract : Fast electron transport path of a simple metal oxide with distorted crystal structure is demonstrated by measuring the electron transport properties of the NbO2 epitaxial films grown on α‐Al2 O3 substrates. Experimentally obtained electron carrier effective mass in the [11 2 ¯ ] direction is surprisingly small (0.051 me ), demonstrating quasi 1D conductivity of NbO2 .